Wild instinct : a novel - Parker, T. Jefferson (Minotaur Books, 2025)
"The hunt for the truth is the deadliest game. Lew Gale, a former Marine sniper, now an Orange County California Sheriff's detective, is assigned to track and shoot a mountain lion that has killed a man in Caspers Park, located in the rugged country east of Laguna Beach, California. The victim is Bennet Tarlow, a rich developer and man-about-town in upscale coastal Orange County. The investigation takes a chilling turn when Lew and his new partner, Daniela Mendez, discover that Bennet was dead long before the lion got to him. And while Bennet might have been the first to die, he certainly will not be the last"--